Antifungal and antifeedant terpenoids from Paraphaeosphaeria sp. cultured by extract of host Ginkgo biloba. (June 2023) - Su, Shuang; Yang, Xue-Qiong; Yang, Ya-Bin; Ding, Zhong-Tao
Abstract: Five undescribed terpenoids including a polyketide-terpenoid hybrid paraphaone, and four eremophilane sesquiterpenoids, paraphaterpenes A-D, as well as two known compounds were isolated from the endophytic fungus Paraphaeosphaeria sp. cultured by extract of host Ginkgo biloba L. The structures were established by spectroscopic analyses, and the single-crystal X-ray diffraction. The antifungal activity of Paraphaeosphaeria sp. cultured by extract of G. biloba against the plant pathogen Alternaria alternata was significant and higher than that of PDB medium. Tested compounds indicated antifeedant activities against silkworms with feeding deterrence index at 10–70%. Paraphaone, paraphaterpenes A, C, D and alternariol methyl ether showed significant antifungal activities against the phytopathogens A. alternata, Aspergillus fumigatus, and entomopathogen Beauveria bassiana with MICs ≤4 μg/mL. And the preliminary structure-activity relationship of eremophilane sesquiterpenoids was exhibited. The culture of Paraphaeosphaeria sp. by host G. biloba medium afforded agricultural antibiotics. Graphical abstract: Image 1 Highlights: Five undescribed terpenoids were found from Paraphaeosphaeria sp. The meroterpenoid, sesquiterpenoids, and alternariol derivative showed significant antibiosis. The interaction of Paraphaeosphaeria sp. and host G. biloba induced the antifungal activity. The structure-activity relationships of eremophilane sesquiterpenoids were indicated.